Inclusive Development of Rural-Urban Agglomerations of Ukraine: Capacity, Sectoral and Socio-Economic Orientation, Trends - Pavlov Oleksandr; Pavlova Iryna; Pavlov Oleksandr; Didukh Serhii; Lagodiienko Volodymyr (European Countryside, 2024)
Ukraine, as a large Central European country, because of its available natural resources, has stable traditions of agriculture. However, the unsatisfactory state of the rural socio-spatial environment, the low standard of living of the rural population do not correspond to the country's achievements in the field of agricultural production. The reform of decentralization of public power and management, launched in 2015, created prerequisites for solving not only the problems of rural development but also overcoming spatial disparities, inequality in the incomes of the rural and urban population. The article presents a view of United Territorial Communities and new districts as rural-urban agglomeration formations that differ from urban agglomerations in terms of population, resources and functions. The inclusive capacity, sectoral and socio-spatial focus, development trends of these agglomerations based on inclusiveness are determined. These processes have many common features and characteristics that are characteristic of similar socio-spatial formations of other countries, which gives the investigated problems international significance. Solving the problems formulated and solved in the article will contribute to the successful post-war reconstruction of Ukraine on an inclusive basis.